Regulatory Nucleotide Sequence Signals for Expression of the Genes Encoding Ribosomal Proteins - Ryu, Jihye; Lee, Chaeyoung (Frontiers in Genetics, 2020)
Ribosomal proteins (RPs) are essential components that translate genetic information from mRNA templates into proteins. Their expressional dysregulation adversely affects the survival and growth of human cells. Nevertheless, little is known about the nucleotide sequences regulating the expression of RPs. Genome-wide associations for expression level of 70 RP genes were conducted across expression stages. Eighteen expression regulatory quantitative trait loci (erQTL) were identified for protein abundances of 21 RPs (P < 1 × 10−5), but not for their mRNA expression and ribosome occupancy (P > 1 × 10−5). These erQTLs for protein abundance (pQTLs) were all trans-acting. Three out of the pQTLs were associated with the expression of long non-coding RNAs (lncRNAs). Target genes of these lncRNAs may produce ribosomal components or may control the metabolic cues for ribosome synthesis. mRNA of the RP genes extensively interact with miRNAs. The protein-specific erQTLs may become engendered by intensive miRNA controls at the translational stage, which in turn can produce RPs efficient in handling instantaneous cell requirements. This study suggests that the expression levels of RPs may be greatly influenced by trans-acting regulation, presumably via interference of miRNAs and target genes of lncRNAs. Further studies are warranted to examine the molecular functions of pQTLs presented in this study and to understand the underlying regulatory mechanisms of gene expression of RPs.